Malaysian university undergraduates' perceptions towards comprehensive online instructions amidst COVID-19 - Nor Azikin, Mohd Omar; Zailani, Jusoh; Shaidatul Akma, Adi Kasuma (2020)
The global pandemic COVID-19 has halted all face-to-face educational meetings and shut down academic institutions. Educational activities, are therefore, undertaken remotely at the safe comfort of individuals’ home. This unprecedented situation calls for a research on university students’ perceptions and their readiness for comprehensive online instructions. Thus, this study primarily aims to investigate these issues further. The questionnaire was distributed to the students in higher institutions in Malaysia through the link of Google Form. Findings indicated that students’ readiness for online learning is not optimal, and they require a lot of support from universities and lecturers in areas of financial assistance, internet accessibility, timely feedback on assessments and constant academic engagement. However, there is an indication that suggests students studying at research universities (RUs) have more positive perceptions towards online instructions, than those in non-research universities (NRUs) - which might be due to RUs’ better establishment of learning facilities, equipment, resources and pedagogical approaches. In ensuring continuity of learning amidst this trying time, the pedagogical approaches to teaching and learning must change. All stakeholders from practitioners, students, parents and families, government and private sectors, education markets, academic institutions and the public at large must be responsible and contribute to realising the best possibleonline learning environment for the current and future generation of learners.